INTERACTIVITY AND DYNAMISM OF MODERN TRANSFORMATIVE OBJECTS IN THE CONTEXT OF THE ARTISTIC APPROACH TO DESIGN - Гладчук, М. Ю. (Art and Design, 2021)
Purpose: the objective of this study is to offer the classification of design objects with variable geometry by the criteria which specify qualitative characteristics of dynamics and interactivity of their transformation within the framework of artistic approach to design. Methodology. In this study both general and special research methods are used, the most relevant being the method of analysis of a sample of design objects with variable geometry by creating a descriptive matrix based on specified criteria. Results. Two criteria were identified, relevant to this study, namely the “nature of the transformation dynamics” and “the degree of audience involvement in the transformation process”. The nature of the transformation dynamics criterion takes into account the factors and conditions necessary to ensure the functioning of the transformation process of the object. This factors and conditions determine the specificity of the object-environment interaction and its corresponding expected or, conversely, spontaneous transfiguration. Design objects according to this criterion are divided into two types. The degree of audience involvement in the transformation process criterion takes into account the existence and options of the object-audience interaction, and determines the nature of its impact on the process of transformation of the object (or lack thereof). In this case, eight types of objects were determined. Scientific novelty. The analysis of transformational objects of conceptual design and art (constructed within the artistic approach to design) in terms of qualitative evaluation of their interactivity, dynamism, and the level of audience involvement (direct or indirect) in the process of their transformation was performed; criteria for qualitative evaluation of these characteristics were derived and results were summed up in the accordant typology. Practical significance. The obtained results are key to understanding the role and specifics of objects with variable geometry in the context of modern design and allow the further identification of the most relevant trends in design of such objects with the acknowledgement of the modern visual culture.